Entre cactus e palmeiras: limites e possibilidades da construção da memória nos arquivos da UFAL - Silva, Laila Leandro Vieira da (2019)
The University has as its mission to develop scientific and technological knowledge, making possible the promotion of services and products for society. The university archive with its informative potential, testifies to the institution’s memory and enables mechanisms that evidence social memory. Information stored and preserved in university archives enable the development of new researches, since custodial records encourage intellectual and scientific development and progress. Thus, this research searched to analyze the potentialities generated by the technicalinstrumental actions in the processes of information transfer in the Campuses archives of the Federal University of Alagoas, considering its impact in the construction of the institutional memory and of the society of Alagoas. As a methodological assumption we adopted documentary research, with a qualitative character, correlated with the accomplishment of interviews with the servers of the Campuses archives of the institution. To think about the limits and possibilities of the construction of memory in the archives of the Federal University of Alagoas is to understand the symbolic, material, structural and socioeconomic conditions that the institution is inserted in its 58 years of creation. We understand that the UFAL Campuses archives constitute a very rich information source, offering society information that can help in their needs.